Buku Tamu Berbasis Web Pada Dinas Komunikasi Dan Informatika Kota Banjarbaru - Reka Nur Andinni (Journal Information Technology Trends (JITRENDS), 2025)
The manual guest book system currently used at the Communication and Informatics Service of Banjarbaru City presents several challenges, including the risk of data loss, difficulties in archive retrieval, the absence of a service satisfaction questionnaire, and a lack of transparency regarding employee attendance information. This study aims to design and build a web-based guest book information system to optimize visitor data management, provide a satisfaction questionnaire facility, and display real-time employee attendance information. The system development methods include system modeling, database design (ERD), web application development, and system testing. The results of this study produce a digital system that simplifies the recapitulation and printing of visitor data, streamlines service time, and improves information transparency for the public visiting the Communication and Informatics Service of Banjarbaru City.